Prototype design of AR-based flipbook with local wisdom for reading media - Afnita, Afnita; Amir, Amril; Olva Zuve, Farel; Mohamed Mokhtar, Marzni; Fadil, Al Khansa Humaira; Li’idaini, Iflah (BAHASTRA, 2026)
This research is motivated by a critical educational paradox in West Sumatra, where high public reading interest indexes contradict the low functional reading competence among secondary school students. This cognitive discrepancy is primarily caused by the reliance on nationally standardized teaching materials that alienate students from their socio-cultural environment. To address theoretical and practical gaps in digital ethnopedagogy, this research aims to systematically design a conceptual blueprint of an interactive flipbook prototype that utilizes Augmented Reality (AR) to materialize abstract Minangkabau cultural concepts. The methodology employed in this research is a descriptive-analytical approach focused specifically on a preliminary study and conceptual design. The scope of this research is deliberately delimited to comprehensive needs analysis and structural product design. Empirical data were gathered from eighth-grade students and teachers at SMP Negeri 7 Padang through questionnaires, interviews, and document analysis, utilizing ethnopedagogy as an analytical tool and cognitive multimedia theories as a reference framework. The findings of this research empirically confirmed a critical demand for interactive visual media rooted in the socio-cultural environment. Based on these needs, the design phase in this research successfully formulated a pedagogically sound blueprint integrating the 5M scientific approach with immersive 3D AR features, wherein local cultural icons are represented as analytical case studies for popular scientific texts. In conclusion, this research establishes a novel pedagogical framework synergizing immersive technology and local wisdom. For future academic endeavors, transitioning from the structural blueprint of this research to empirical technological development is highly recommended to quantitatively evaluate its effectiveness in improving reading literacy.